Evaluation of groundwater resources on the coral islands of Lakshadweep, India - Singh, Vijay Shankar (Springer, 2017)
This book provides insights on and tools for the characterization of island aquifers, as illustrated by the example of the coral islands of Lakshadweep in India. After an initial overview of the different coral islands, subsequent chapters explain key geophysical, hydrogeological and hydrochemical methods for the assessment and characterization of coral island aquifers. The book's closing chapters highlight selected case studies and describe actual implementations of the methods discussed. In addition to presenting the details of data collection on each island - a valuable resource for any future study on these islands - in graphical form, the book proposes suitable measures for ensuring the sustainability of groundwater resources on the islands. Accordingly, it offers a unique and essential source of information for all hydrogeologists whose work involves island aquifers.
Keywords: Groundwater -- India -- Lakshadweep.; Coral reefs and islands -- India -- Lakshadweep.; India -- Lakshadweep.; elektronické knihy; electronic books